International research outputs of Can Tho University: The first, the most, and the top - Thi Ngoc Nhung Tran; Ngoc Linh Le (CTU Journal of Innovation and Sustainable Development)
This research reviews the expansion of academic literature generated by Can Tho University (CTU), as indexed on Scopus, Web of Science (WoS), and Dimensions databases. We examine various aspects of CTU's international research outputs, including domains of study, author data, publication statistics, and citation counts. The results reveal that both the quantity and quality of CTU's international research papers have steadily increased over the years. These findings are expected to provide CTU's leaders, administrators, and scholars with a comprehensive overview of the institution's research landscape over recent periods, enabling them to make well-informed decisions regarding the future direction of its research mission.